POLA SEBARAN DAN ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN DEMAM BERDARAH DENGUE - Tanjung, Risnawati; Jernita Sinaga; Helfi Nolia; Devyana Sembiring; Dea Hutagalung (Poltekkes Kemenkes Medan, 2024)
Dengue hemorrhagic fever (DHF) is a disease that causes death, known for > 200 years, and has become a health problem in the world, especially in developing countries, including Indonesia. Deli Serdang Regency had the highest number of cases in North Sumatra Province in 2019 with 1,326 cases, in 2020 there were 974 cases, IR: 50.4. In 2021, the Regency/City ranked 14th out of 514 Regency/City in Indonesia for the highest number of dengue fever cases in 2021 with 803 cases, IR/morbidity rate: 34.63/100,000 population, CFR/death rate: 0.12%. It is possible to identify the location of the patient to the address of the individual's location, so as to obtain information regarding the distribution pattern of cases in each region using the Geographic Information System (GIS) and analysis of factors related to the incidence of dengue hemorrhagic fever.This type of research is analytical observation with a case control approach. The sample in this study was all people living permanently in the working area of ??the Tanjung Morawa Community Health Center, totaling 48 respondents, 24 cases and 24 controls. The sampling technique was carried out using Simple Random Sampling, data was analyzed using the Chi Square test. Based on the research results, it shows that the variables related to the incidence of dengue fever are knowledge (p-value = 0.00; OR = 0.06), attitude (p-value = 0.00; OR = 21), 3M PSN (Mosquito Nest Eradication) actions Plus (p-value=0.000; OR=17) and unrelated variables are occupation (p-value=0.029; OR=0.23) and age (p-value=0.081; OR=0.29). It is recommended that the community health center be better able to increase public understanding about the management and prevention of dengue fever.